Perspective and Impact of Islamic Business Ethics on Consumer Satisfaction at Anita Bakery, Bangkalan City - Muhammad Zaini; Abdur Rohman (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
This study aims to analyze the effect of Islamic business ethics on consumer loyalty at Anita Bangkalan bakery through the variables of consumer commitment trust and relationship benefits. The population in this study were consumers of Anita Bangkalan bakery. Sampling using Incidental Sampling technique with selected criteria. The results showed that in Islamic business ethics on consumer pleasure at Anita Bangkalan bakery is (1) consumer pleasure has no effect on consumer loyalty. This can happen because the commitment in the questionnaire is about service to consumers, which can lead to different perceptions for each consumer. (2) Relational benefits have a significant effect on consumer pleasure because customers receive service benefits such as a sense of security and calm. (3) Simultaneously, consumer willingness, trust and taste have a significant effect on visible consumer pleasure.